Development of Buffer Solution Worksheet Based on Discovery Learning to Improve Students' Critical Thinking Skills - Lathifa, Azzahra Ghina; Yonata, Bertha (Asian Journal of Science Education, 2024)
One of the essential 21st-century skills for students is critical thinking. However, students' critical thinking skills in buffer solution material are relatively low, so appropriate learning models and teaching materials are needed. This research aims to develop worksheet based on discovery learning to improve students' critical thinking skills on buffer solution material, reviewed from validity, practicality, and effectiveness. The method used in this research is Research and Development (RD) with the 4D development model by Thiagarajan, but this research is limited to the development stage. A limited trial was conducted with 15 students from one of the high schools in Surabaya in June 2024. The results showed that the worksheet is declared valid, with a median score of 4 in the valid category. The practicality of the worksheet is stated to be practical in terms of the results of the response questionnaire, namely that students gave positive responses to the worksheet developed and supported by observations of student activities where relevant student activities exceeded irrelevant activities. The worksheet effectiveness is declared effective in terms of the results of students' critical thinking skills tests which had increased with N-Gain scores in the range of 0.64 to 1.00 in the medium to high category and supported by students' knowledge learning outcomes reaching individual completeness, namely 75. Based on these results, it can be concluded that buffer solution worksheet based on discovery learning is feasible for improving students' critical thinking skills in buffer solution material.